CORRIDOR MAPPING OF BIRD AROUND SACRED AREA BASED ON VEGETATION COVER IN WESTERN AREA OF MT. SEMERU USING GEOGRAPHIC INFORMATION SYSTEM (GIS) - Rahmi Ipango; Luchman Hakim (Journal of Environmental Engineering and Sustainable Technology, 2019)
Danyangan is A proof traditional conservation created by local wisdom. Knowledge of bioculture provides a facts play a role in understanding the ecological processes that occur and providing an overview local efforts in protecting the environment. The village’s. Danyangan has the form of a collection of large trees marked by the presence of sacred fig trees (Ficus sp.). Moreover, the fig tree become a habitat for several species of birds. The canopy’s cover reserves water, insects, and fruits as food for birds and creates an interesting relation as a microhabitats.The location of this study was carried out in the administrative district of Malang district in Tumpang, East Java in the area of the district located in Gubugklakah, Kunci, Drigu, Poncokusomo, Puthuk, Pandansari, Jajang, and Aran-aran. Bird observation is carried out using the point count or IPA method.The study recorded 636 individuals consisting of 31 species, 21 families and 9 orders. The birds identified were dominated by Passeriformes as many as 11 families. Based on the results, shows all locations in the danyangan area dominated by detailed Swallow (Collocalia linchii). Instead, The value of bird species abundance in all study locations is included in the high category of values ranging >4.A spatial review is needed to see the extent and potential of danyangan on the western semeru slopes in an effort to conserve biodiversity, especially birds. As inthisstudy, we investigated thecomposition, diversity and Geographic Information System of birds in the Danyangan area.A spatial review is needed to see the extent and potential of danyangan on the western semeru slopes in an effort to conserve biodiversity, especially birds. As inthisstudy, we investigated thecomposition, diversity and Geographic Information System of birds in the Danyangan area.